Hypertension in Moroccan adults: sociodemographic, lifestyle, and dietary risk factors - Lahmam, Houria; Auajjar, Nabila; Mehdad, Slimane; Mekkaoui, Bouchra; El Berri, Hicham; Belakhel, Latifa; Attarassi, Benaissa; Saeid, Naima; Mounach, Samir; El Kari, Khalid; Aguenaou, Hassan (The North African Journal of Food and Nutrition Research, 2025)
Background: Hypertension constitutes a principal etiological factor in cardiovascular morbidity and premature mortality worldwide, however, the epidemiological profile of its risk determinants within the Moroccan population remains inadequately characterized. Aims: This investigation aimed to estimate the prevalence of prehypertension and hypertension and elucidate their association with various sociodemographic, behavioral, and metabolic factors among adult Moroccans. Patients and Methods: Data were derived from the inaugural nationwide cross-sectional survey on non-communicable diseases risk factors, conducted between 2017 and 2018. Data collection adhered to the World Health Organization’s STEPwise approach to surveillance (STEPS). The analytical cohort comprised 4580 adults, aged 18 years and above. Results: The observed prevalence rates for prehypertension and hypertension were 42.4% and 34.5%, respectively. Individuals aged 45 years or older demonstrated a significantly elevated propensity for both prehypertension and hypertension relative to younger cohorts. Participants with university-level education exhibited a statistically significant elevated risk of hypertension compared to those with lower educational attainment. Overweight and obese individuals presented a significantly increased risk for both prehypertension and hypertension than their non-overweight peers (Adjusted Odds Ratio [AOR] = 1.83; 95% Confidence Interval [CI]: 1.58–2.13; p < 0.001; and AOR=3.06; 95% CI: 2.60–3 .60; p < 0.001, respectively). Hyperglycemia and dyslipidemia were associated with higher odds of hypertension, albeit marginally (AOR = 1.19; 95% CI: 0.99–1.41; p = 0.055; and AOR = 1.16; 95% CI: 0.99–1.37; p = 0.069, respectively). Current tobacco smokers exhibited a significantly higher risk of hypertension than non-smokers (AOR = 1.47; 95% CI: 1.09–1.98; p = 0.013). Conclusions: The prevalence of prehypertension and hypertension was substantial within the studied population. Advanced age, elevated educational attainment, obesity, hyperglycemia, dyslipidemia, and tobacco smoking were associated with an elevated risk of both prehypertension and hypertension. Consequently, the implementation of urgent public health interventions is imperative to address the health burden associated with hypertension and to prevent the progression of prehypertension to hypertension and subsequent cardiovascular diseases. Keywords: Age, Dyslipidemia, Education level, Hyperglycemia, Hypertension, Obesity, Overweight, Prehypertension.